KONTRIBUSI PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH DAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH GUNA MENDUKUNG PELAKSANAAN OTONOMI DAERAH (STUDI KOMPARASI PEMERINTAH KOTA SEMARANG DAN SURAKARTA) - Arief Himmawan DN; Djoko Wahjudi (Jurnal Bisnis dan Ekonomi, 2014)
Implementation of the law number 32 in 2004 to encourage local governments to be more independent in governance in their respective regions. This encourages regions to be more independent in all respects, especially financially, because the level of independence of a region can be seen from the high and low revenue. Local taxes and levies are a source of revenue that is highest in Semarang and Surakarta. Data analysis method used by the writer is descriptive analysis of the contribution and effectiveness analysis. The population in this study is the local taxes and levies contained in DPKAD DPPKA Semarang and Surakarta. In the period of 2010-2012 fiscal year revenue contribution of local taxes to be optimal in Semarang with an average contribution of 52.73% per year. While the contribution levies to be optimized PAD in Surakarta with an average contribution of 37.25% per year. The contribution of local taxes to a larger budget in Semarang with the ability to finance the expenditure amounted to 10.45% per year, so that the government of Semarang can be said to be more independent. Contributions levies to bigger budget in Semarang with the ability to finance the expenditure amounted to 5.23% per year, so that the government of Semarang can be said to be more independent. To increase the contribution of local tax revenues and levies to the total revenue and simultaneously increase its contribution to the budget the government of Semarang and Surakarta need to do several steps of which is necessary to increase the intensification of collection types of local taxes and levies, and then carried out extension by way of enacting types tax and new levies in accordance with the conditions and the potential that exists. Keywords: local taxes, levies, local revenue (PAD), budget (APBD).